Current Topics in Lactation 2017
DOI: 10.5772/66526
|View full text |Cite
|
Sign up to set email alerts
|

Postlactational Involution: Molecular Mechanisms and Relevance for Breast Cancer Development

Abstract: Mammary gland tissue changes appearance and functionality in diferent sequential steps. The tissue of virgin, pregnant, or lactating mammary glands changes controlled by inely regulated physiological processes. A fourth stage (involution), triggered upon weaning, involves remodeling, and the gland regresses to resemble a prepregnant stage. This highly complex process characterized by a high degree of epithelial cell death and tissue remodeling can be divided into phases, which can be independent of each other.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…During post-partum mammary gland involution, the immune composition of the gland expands with an influx of infiltrating mast cells, macrophages, neutrophils, dendritic cells and natural killer cells, which remove apoptotic epithelial cells and support the remodeling of the gland (Guo et al, 2017;Kordon and Coso, 2017;O'Brien et al, 2010;Schwertfeger et al, 2001). Since our scRNAseq analyses suggested that fully involuted, post-pregnancy mammary glands are enriched for populations of NKT cells, we next utilized a series of flow cytometry analyses to validate this observation.…”
Section: Pregnancy Induces the Expansion Of A Specific Population Of Nkt Cellsmentioning
confidence: 86%
“…During post-partum mammary gland involution, the immune composition of the gland expands with an influx of infiltrating mast cells, macrophages, neutrophils, dendritic cells and natural killer cells, which remove apoptotic epithelial cells and support the remodeling of the gland (Guo et al, 2017;Kordon and Coso, 2017;O'Brien et al, 2010;Schwertfeger et al, 2001). Since our scRNAseq analyses suggested that fully involuted, post-pregnancy mammary glands are enriched for populations of NKT cells, we next utilized a series of flow cytometry analyses to validate this observation.…”
Section: Pregnancy Induces the Expansion Of A Specific Population Of Nkt Cellsmentioning
confidence: 86%
“…The post-partum mammary gland involution is marked by an influx of infiltrating mast cells, macrophages, neutrophils, dendritic cells, and natural killer cells, which remove apoptotic epithelial cells and support the remodeling of the gland (Guo et al, 2017;Kordon and Coso, 2017;O'Brien et al, 2010;Schwertfeger et al, 2001). Since our scRNA-seq analyses suggested that post-pregnancy mammary glands are enriched for populations of NKT cells, we next used a series of flow cytometry analyses to validate this observation.…”
Section: Pregnancy Induces the Expansion Of A Specific Population Of Nktsmentioning
confidence: 86%